The Effects of Thymoquinone Against Morphine-induced Damages on Male Mice Liver - Salahshoor, Mohammad Reza (Int J Prev Med, 2018)
BACKGROUND: Morphine is a pain medication. It is mostly processed in liver and reasons disturbing effects. It can increase the production of free radicals. Thymoquinone is a phytochemical compound found in the plant Nigella sativa. It has diverse pharmacological properties such as antioxidant and anticancer. This study was intended to assess the effects of thymoquinone against morphine damages on the liver of mice. METHODS: In this study, various doses of thymoquinone (4.5, 9, and 18 mg/kg) and thymoquinone plus morphine was administered (once a day) intraperitoneally to 48 male mice for 20 consequent days. These mice were randomly assigned to eight groups (n = 6). Aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, serum nitric oxide (NO) levels, liver weight, and histology have been studied. RESULTS: The results indicated that morphine administration significantly increased the mean diameter of central hepatic vein and hepatocyte, blood serum NO level, liver enzymes level, and decreased liver weight compared to saline group (P < 0.05). However, thymoquinone and thymoquinone plus morphine administration significantly enhanced liver weight and reduced the mean diameter of hepatocyte, central hepatic vein, liver enzymes, and NO levels in all groups compared to morphine group (P < 0.05). CONCLUSIONS: It seems that antioxidant effect of thymoquinone could protect damage of liver parameters against morphine toxicity.